81.1k views
0 votes
83=4k-7(1+7k) How to solve

2 Answers

6 votes

Answer:

k = -2

Explanation:

Step 1: Use 7 to open the bracket :

-7(1+7k)=-7-49k

Step 2: Collect like terms

Step 3 : Divide both sides of the equation by -45


83=4k-7(1+7k) \\ \\83 = 4k-7-49k\\\\ 83+7=4k-49k\\\\90 = -45k\\\\(90)/(-45) = (-45k)/(-45) \\\\k = -2

User Bornfromanegg
by
5.6k points
4 votes

Answer:

k = -2

Explanation:

83=4k-7(1+7k)

Distribute

83=4k-7-49k

Combine like terms

83 = -45k -7

Add 7 to each side

83+7 = -45k-7+7

90 = -45k

Divide each side by -45

90/-45 = -45k/-45

-2 = k

User Pingze
by
6.2k points